THE IMPLEMENTATION OF PHARMACEUTICAL SERVICE STANDARDS IN PHARMACIES OF ROKAN HULU DISTRICT - Situmorang, Manotar; Saman; Basyariah Lubis (Jurnal FARMASIMED (JFM), 2023)
Currently, pharmaceutical services have experienced a lot of development, which initially used to focus on drug management, but have now turned into drug and clinical pharmacy services aimed at raising the standard of living of patients. Pharmaceutical applications are carried out according to pharmaceutical service standards in pharmacies which serve as the basis for providing services. Minister of Health Number. 73 of 2016 is a benchmark that is always guided by pharmaceutical staff in providing services. In this research, qualitative research was chosen which is descriptive quantitative through a cross sectional approach. The sample is determined using the Non-Probability Sampling technique, namely the Total Sampling type where the total population is determined as a sample. Where the number of samples selected amounted to 25 people. Research data must be in-depth, clear, and specific through in-depth interviews and observations. Data analysis was performed on variables through univariate analysis and bivariate analysis using the Chi Square test with a 95% confidence level. Aspects of infrastructure, Management of Pharmaceutical Supplies and Health Supplies, and administration have a significant relationship to pharmaceutical services at pharmacies in Rokan Hulu district with each sequential p-value being 0.002; 0.003; and 0.003. In improving services in accordance with Permenkes Number. 73 of 2016, it requires qualified facilities and infrastructure, good health management and provision, as well as complete administration.